Lunar core structure investigation: Implication of GRAIL gravity field model. Issue 6 (15th March 2015) - Yan, Jianguo; Xu, Luyuan; Li, Fei; Matsumoto, Koji; Rodriguez, J. Alexis P.; Miyamoto, Hideaki; Dohm, James M.
Abstract The details of the structure of the core are important to understanding the evolution and thermal history of the Moon. Even with existing information, including seismic measurements from the Apollo mission, as well as geodetic measurements from Lunar Laser Ranging (LLR) data and gravity, it is still difficult to constrain the size of the lunar core and its density with certainty. Here, we investigate the radius and density of the lunar core using simple constraints of the estimated mean density and mean moment of inertia of the Moon with the help of a Monte Carlo simulation algorithm. This includes a comparison between the results based from the more recent GRAIL gravity field model GRGM660PRIM with those of the gravity field model SGM100h. Analysis through an improved gravity field model indicates that the lunar core is smaller and denser than previously estimated, and the result (a core radius with 370 km) is consistent with more recent result.